Identification of bioactive compounds in leaves and fruits of Actinidia arguta accessions from northeastern China and assessment of their antioxidant activity with a radical-scavenging effect. Issue 1 (1st January 2021) - Tan, Changhua; Wang, Zhigang; Feng, Xiuli; Irfan, Muhammad; Changjiang, Liu
Abstract: Actinidia arguta (Sieb. et Zucc.) is abundant of vitamin C and bioactive compounds with high antioxidant activities. In this study, eight wild A. arguta accessions from different areas in Northeast China were collected. Some bioactive compounds were extracted from leaves, petioles and fruits of different germplasms for constituent analysis and non-enzymatic antioxidant assay. Liquid chromatography with tandem mass spectrometry (LC–MS/MS) was used to detect the flavonoid compounds. The results showed that the highest vitamin C content was found in young apical leaves of 'CBS-6' (7.47 mg/g fresh weight), and the highest soluble sugar content was in fruits of 'CJ-1' (196.52 mg/g fresh weight) and the highest total phenolic content and total flavonoids content were in young apical leaves of 'CBS-11' (3.48 mg/g fresh weight) and of 'CBS-3' (2.00 mg/g fresh weight), respectively. Ten flavonoid compounds including kaempferol, isorhamnetin and quercetin were detected in leaves, petioles and fruits. The total content of flavonoids was highest in young apical leaves (10219.84 µg/g) and the lowest in fruits (78.75 µg/g). Based on the comparison of the contents of several bioactive compounds, the two accessions 'CJ-1' and 'CBS-8' stood out; the young leaves had the strongest antioxidant activity among different tissues based on the non-enzymatic antioxidant assay. These results highlighted the radical-scavenging potential in vitro of A. arguta leaves as a major source of phenolics and vitamin C as well as flavonoids. It provided a theoretical basis for the utilization of leaves of A. arguta . Supplemental data for this article is available online at https://doi.org/10.1080/13102818.2021.1908166 . Supplemental data for this article can be accessed online at https://doi.org/10.1080/13102818.2021.1908166 .